The role of extensive margins of exports in The Great Export Recovery in Germany, 2009/2010 - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2013)
This paper contributes to the literature by documenting for the first time the contribution of adding (and dropping) goods and destination countries to the sharp increase in exports of goods in the German economy as a whole during the Great Export Recovery in 2009/2010. The empirical investigation finds that firms that exported in both 2009 and 2010 are much more important for the export dynamics than export starters and export stoppers. Firms that increased their exports (and that were the drivers of the export boom) exported on average more goods and to more destination countries in 2009 than firms that decreased their exports, and they increased both extensive margins of exports on average while firms with decreased exports reduced both the number of goods exported and the number of countries exported to. These empirical regularities can be linked to recent theoretical models of multiproduct, multiple-destination exporters that point to a positive link between firm productivity and both extensive margins of exports. Although the data do not allow a direct test of the hypothesis, the evidence at hand justifies that we can argue that the more productive firms with higher and increasing extensive margins of exports are the drivers of The Great Export Recovery of 2009/2010 in Germany.
Keywords: F14; 330; extensive margins of exports; The Great Export Recovery; Germany